Narasi Self-help Generasi Z dan Masyarakat Tradisional: Sebuah Kajian Produksi Kebudayaan - Anjarsari, Fitrilya; Istiningdias, Dini Sri (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This research will focus on the increase in sales of popular fiction works in the self-help genre, with the aim of understanding the reasons behind this growth. In accordance with the prevailing principles of production, an augmentation in sales is naturally attributable to the alignment of market interest and the producer's strategy for its fulfilment. Nevertheless, employing the notion of cultural production, this pertains to the process of establishing a connection between the conventional principles concerning mental well-being that are held by Generation Z and those that have been handed down through the generations. The dissemination of such principles within a cross-generational cultural milieu is undoubtedly predicated on the implementation of a meticulously devised strategy, one that is designed to ensure its acceptance. This constitutes the novelty of this research, namely that popular literary production is not invariably viewed from a commercial standpoint.